Architectural design studio: Embracing a transdisciplinary approach (EAAE Annual Conference Proceedings, 2023)
The Co-creation design studio, at the Department of Architecture, University of Cyprus, has been acting as a meeting place for students, educators, researchers, citizens, and external stakeholders since 2021, aiming to bridge gaps between architectural research, pedagogy, civil society, and local governance bodies through a transdisciplinary pedagogical framework.